Abdominal and robotic sacrocolpopexy costs following implementation of enhanced recovery after surgery. Issue 2 (9th January 2023) - Baker, Mary V.; Teles Abrao Trad, Ayssa; Tamhane, Prajakta; Weaver, Amy L.; Visscher, Sue L.; Borah, Bijan J.; Klingele, Christopher J.; Gebhart, John B.; Trabuco, Emanuel C.
Abstract: Objective: To compare perioperative costs and morbidity between open and robotic sacrocolpopexy after implementation of enhanced recovery after surgery (ERAS) pathway. Methods: The present retrospective cohort study of patients undergoing open or robotic sacrocolpopexy (January 1, 2014, through November 30, 2017) used an ERAS protocol with liposomal bupivacaine infiltration of laparotomy incisions. Primary outcomes were costs associated with index surgery and hospitalization, determined with Medicare cost‐to‐charge ratios and reimbursement rates and adjusted for variables expected to impact costs. Secondary outcomes included narcotic use, length of stay (LOS), and complications from index hospitalization to postoperative day 30. Results: For the total of 231 patients (open cohort, 90; robotic cohort, 141), the adjusted mean cost of robotic surgery was 3239 higher compared with open sacrocolpopexy (95% confidence interval [CI] 1331–5147; P < 0.001). Rates were not significantly different for intraoperative complications (robotic, 4.3% [6/141]; open, 5.6% [5/90]; P = 0.754), 30‐day postoperative complications (robotic, 11.4% [16/141]; open, 16.7% [15/90]; P = 0.322), or readmissions (robotic, 5.7% [8/141]; open, 3.3% [3/90]; P = 0.535). The percentage of patients dismissed on postoperative day 1 was greater in the robotic group (89.4% [126/141] vs. 48.9% [44/90], P < 0.001). Conclusions: Decreased LOS associated with ERAS provided significant cost savings with open sacrocolpopexy versus robotic sacrocolpopexy without adverse impacts on perioperative complications or readmissions. Synopsis: Decreased length of stay with enhanced recovery after surgery provided significant cost savings for patients undergoing open compared with robotic sacrocolpopexy with similar perioperative outcomes.